Conceptual and empirical aspects of the financing of new companies in Colombia - Barona Zuluaga, Bernardo; Gómez Mejía, Alina (Cuadernos de Administración, 2010)
This article presents the results of an empirical research on the type of financial resources used by a sample of new enterprises in their early years of life. The main conceptual support of the study is the financial growth cycle paradigm developed by Berger and Udell (1998). This paradigm successfully explains the findings in the empirical component of the study presented here, which is based on a survey of 130 entrepreneurs in the city of Cali, Colombia. The survey results highlighted the importance of the use of financial resources provided by the owner and theirs family and friends, and of the retention of profits in their companies in the early years. Next in importance is the funding provided by credit institutions; attention is called to the relative importance of leasing. The most important recommendations include the strengthening of institutions and mechanisms that provide seed and venture capital to new enterprises, to give greater weight in finance courses at University level to the study of the problems of new companies and MSMEs, to promote a financial reform to facilitate to small and medium size companies the issue of shares, and to improve the quality and quantity of public financial information available regarding these kinds of enterprises.